Ethical implications of preimplantation genetic diagnosis (pgd): a qualitative study on three selected groups in Malaysia / Angelina Patrick Olesen - Patrick Olesen, Angelina (2013)

(untitled)
Pre-implantation genetic diagnosis or PGD refers to procedure performed on embryos prior to implantation in IVF trials. The technology enables the embryo to be screened for genetic disease and is usually applied when parents have risk of genetic diseases. Ethical issues raised from the utilization of PGD include gender biasness and discrimination towards people with disabilities often linked to societal obsession with perfectionism. This study explores participant perception of ethical issues posed by PGD, by focusing on four key themes: sanctity of life, play God, perfectionism and freedom of choice. Three focus groups were selected; medical personnel, religious representatives and potential users. Key findings show significantly differing views of each study group. For example, members of the medical fraternity alluded to biological interpretations such as „mere accumulation of cells‟ when declaring limited moral rights of the embryo. On the theme „play God‟ doctors argue that PGD is merely a form of medical but necessary intervention and do not agree with the idea of „meddling with nature‟. Perception of both religious figures interviewed and potential users show mixed and almost similar reactions, whereby some consider PGD as an act of playing God because of the belief that such actions will bring upon unknown and undesirable (but God-ordained) consequences while others believe that actions that prevent dangerous diseases in children would not entail playing God.